EXPRESSION OF CTFAD2 GENE FOR EARLY SELECTION IN SAFFLOWER OLEIC/LINOLEIC OIL CONTENT - I. Buyuk; E. Bolukbasi; S. Aras (Journal of Animal and Plant Sciences, 2016)
Safflower oil constitutes an important source of oleic acid and linoleic acid which can be used for food and industrial applications. Because of their importance, nowadays, breeders are focused on selection of high-oleic or linoleic safflower breeding lines for particular end use purposes. For this aim, we investigated the expression levels of six CtFAD2 genes at leaf and root tissues of four Turkish safflower varieties (LINAS, OLAS, Remzibey-05 and Dincer) by qRT-PCR to find out suitable genes for the early selection of safflower lines with desired oleic/linoleic content. qRT-PCR results showed that all the genes exhibited differential expression levels among different safflower varieties. The highest mRNA levels of all CtFAD2 genes in the leaves were observed in LINAS safflower variety which is a high-linoleic type safflower variety having high yielding and high oil capacity. Among all six CtFAD2 genes, mRNA levels of CtFAD2-1, CtFAD2-5 and CtFAD2-10 genes were interestingly quite similar among leaf tissues of all safflower varieties. Results of the current study suggest that, according to their expression levels in leaf tissues, CtFAD2-10, CtFAD2-5 and CtFAD2-1 genes are appeared as good candidates for early selection of high oleic/high linoleic safflower varieties and can be conveniently used in breeding studies.
Keywords: CtFAD2; safflower; qRT-PCR; oleic; linoleic